RAA System and Exercise Relationship - Sadettin Ünsal; Suleyman Patlar (Türk Spor ve Egzersiz Dergisi)
In this review, it is aimed to discuss the possible interactions between renin-angiotensin-aldosterone system and exercise for health and performance and to present new literature on this subject. From this point of view, an analysis of the experimental and clinical studies on this subject has been made. Physical exercise leads to a number of changes in the plasma levels of renin, angiotensin, and aldosterone, which represent the adaptation of the human body to a new biological environment. Significant (P lt;0.05) increases occur in the levels of plasma renin, angiotensin and aldosterone especially in submaximal and maximal exercise intensity. Hormone levels return to normal with the end of the exercise. Factors such as age and gender, menstrual cycle, salt intake, posture, thermal tension, elevation, training, type of exercise have a major impact on the response of the RAA system to exercise. A relationship between physical activity and permanent endocrine changes could not be demonstrated.